Novel Application of K-Means Algorithm for Unique Sentiment Clustering in 2024 Korean Movie Reviews on TikTok Platform - Baiq Rima Mozarita Erdiani; Aryo Yudo Husodo; Ida Bagus Ketut Widiartha (Universitas Bumigora, 2025)
In recent years, social media has become one of the main factors influencing public perception of films. As a rapidly growing video-sharing platform, TikTok plays a crucial role in shaping audience opinions through comments, short reviews, and user discussions. This phenomenon is increasingly relevant in the Korean film industry, attracting global attention with its diverse genres and engaging narratives. However, a deep understanding of how audiences respond to films based on genre remains limited, especially in the dynamic context of social media. Therefore, this study aims to analyze audience sentiment toward Korean films released in 2024 on TikTok, focusing on sentiment distribution across four main genres: comedy, romance, action, and fun stories. The research methodology includes data collection through web crawling on TikTok, followed by text preprocessing and feature extraction using IndoBERT. Sentiment classification uses SentimentIntensityAnalyzer to categorize comments into positive, negative, or neutral. Since the dataset consists of unlabeled text, K-Means clustering is employed to identify sentiment groupings, with validation using principal component analysis to ensure cluster quality. The findings indicate that the romance and comedy genres are predominantly associated with neutral sentiment, reaching 89.6% and 87.4%, respectively. In contrast, the action genre exhibits higher sentiment polarization, with 14.9% positive and 24.7% negative sentiment. The fun story genre shows a more evenly distributed sentiment pattern. The main challenges include determining the optimal number of clusters and addressing imbalanced sentiment distribution across genres. This study provides valuable insights for filmmakers and marketers to understand audience reactions on social media better, enabling more targeted promotional strategies. Additionally, it contributes to the literature on sentiment analysis in the film industry, emphasizing the importance of genre-specific audience reception patterns for future research.